Simulation and Optimization of Metro Train Braking Rate under the Timing Condition - PAN Yang (Chengshi guidao jiaotong yanjiu)
［Objective］ With the proposal of a green and low-carbon development goal for urban rail transit in China, metro is facing a daily increasing pressure of energy saving and emission reduction. Since traction consumes the main energy in metro operation, it is necessary to conduct a study on the optimization of traction energy consumption. ［Method］ In consi-deration of the low train braking rate in the process of metro design and operation, an energy-saving operation strategy is proposed by appropriately increasing the train braking rate and lowering the maximum cruising speed under fixed interval running time condition, that is, under the timing condition. Based on the establishment of the train traction simulation calculation model, a calculation method under the timing condition is proposed. The feasibility of the model is verified through case simulation, and the impact of the braking rate on traction energy consumption is mainly analyzed. ［Result & Conclusion］ Simulation calculation is conducted on a flat and straight interval, results showing that under the timing condition, the larger the maximum cruising speed of the train is, the more sensitive it is to the change of the braking rate. In the initial period, the increase of train braking rate can obviously bring down the maximum cruising speed of the train, achieving the effect of reducing the traction energy consumption. The feasibility of the energy-saving strategy and its effect are further verified on a specific interval of Guangzhou Urban Rail Line 22. The results show that under the timing condition, when the braking rate on the interval is increased from 0.6 to 0.85, the maximum cruising speed of the train can be reduced from 141 km/h to 117 km/h, saving 30% of the energy consumption with a significant energy-saving effect. As a conclusion, the train braking rate can be appropriately increased in the metro design and operation to save traction energy consumption.